Development and Implementation of a Standard Assessment Battery Across the Continuum of Care for Patients After Stroke. (February 2023) - Lien, Peiting; Deluzio, Sandra; Adeyemo, Jessica; Langton-Frost, Nicole; Lavezza, Annette; Daley, Kelly; Friedel, Stacey; Pruski, April; French, Margaret A.; Raghavan, Preeti
Abstract: Stroke rehabilitation occurs across the continuum of care starting in the acute hospital and through the inpatient and outpatient settings. Rehabilitation aims to minimize impairments and maximize function in individuals after stroke. Because patients often undergo rehabilitation for extended periods, longitudinal assessment of impairment, activity, and participation can facilitate the evaluation of patients' progress toward recovery, as well as communication and decision making to guide clinical practice regarding the intervention(s) to be used and may also be leveraged for clinical research. However, the clinical implementation of a standard assessment battery that spans the continuum of care for patients after stroke is challenging because of operational and time constraints. Here, we describe the development and implementation of a standard assessment battery across the continuum of care by physical therapists, occupational therapists, and speech-language pathologists at the Sheikh Khalifa Stroke Institute. We specifically describe our experience in (1) identifying the core team to lead the process, (2) selecting the measures for the standard assessment battery, and the timeframe for administration, and (3) implementing the standard assessment battery in routine clinical practice.